2016
DOI: 10.1074/jbc.m116.719575
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aromatic Amino Acids in Lipopolysaccharide and Membrane Interactions of Antimicrobial Peptides for Use in Plant Disease Control

Abstract: KYE28 (KYEITTIHNLFRKLTHRLFRRNFGYT-LR), the representative sequence of helix D of heparin co-factor II, was demonstrated to be potent against agronomically important Gram-negative plant pathogens Xanthomonas vesicatoria and Xanthomonas oryzae, capable of inhibiting disease symptoms in detached tomato leaves. NMR studies in the presence of lipopolysaccharide provided structural insights into the mechanisms underlying this, notably in relationship to outer membrane permeabilization. The three-dimensional solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 58 publications
2
41
1
Order By: Relevance
“…Therefore, the pi‐stacking interactions promoted by aromatic residues are not necessary for LPS binding suggesting that only hydrophobicity (and charge) is relevant for this interaction. This is in contrast to the reported relevance of aromatic residues in AMP and LPS binding …”
Section: Resultscontrasting
confidence: 88%
“…Therefore, the pi‐stacking interactions promoted by aromatic residues are not necessary for LPS binding suggesting that only hydrophobicity (and charge) is relevant for this interaction. This is in contrast to the reported relevance of aromatic residues in AMP and LPS binding …”
Section: Resultscontrasting
confidence: 88%
“…Taken these into consideration, C-terminal amidation of the modified peptide may also facilitate to its antimicrobial activity by stabilizing membrane interactive peptide structure and improving the partial charge of the modified analog. Last but not least, a phenylalanine residue might also provide extra membrane- binding driving force for nigrocin-HLM since it contains an aromatic ring (Lee et al, 2013; Datta et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cupiennins mutated with an alanine or lysine in place of phenylalanine residues in their N‐terminal region exhibited decreased lipid‐bilayer interaction . Additionally, Datta et al showed that disruption of aromatic packing in the KYE28 peptide attenuated its antibacterial activity …”
Section: Discussionmentioning
confidence: 99%